GAYA BAHASA KIASAN DALAM LIRIK LAGU BAND “EFEK RUMAH KACA” ALBUM “EFEK RUMAH KACA, KAMAR GELAP, SINESTESIA”. - Khoirul Anwar, Mohamad; Anwar, M. Shoim (Universitas PGRI Adi Buana Surabaya, 2019)
The art of music is so interested by all humans without exception, from the old, youth,teenagers, until the children itself. With a variety of musical genres, the interesting things in music itself is in the lyrics of songs that contain explicit meanings created by the author toexpress the results of his work to be enjoyed by the public. Each author is able to create his workin various ways, through observation, the stories of others, or even his own personalexperience.The purpose of this study is to describe more deeply and thoroughly about thefigurative style in the lyrics of the band 's